Sub-population differences in the relationship between the neighborhood environment and Latinas' daily walking and vehicle time. (March 2018) - Serrano, Natalicio; Perez, Lilian G.; Carlson, Jordan; Patrick, Kevin; Kerr, Jacqueline; Holub, Christina; Arredondo, Elva M.
Abstract: Background: Over 60% of Latinas report not meeting moderate to vigorous physical activity (MVPA) guidelines of 150 min/week. Ecological models of health posit that intrapersonal and environmental factors interact with one another to influence physical activity. Understanding their interactions in relation to transportation behaviors may inform interventions to increase Latinas' physical activity. Purpose: To 1) objectively estimate walking and vehicle time in Latinas, 2) examine the association of, and interactions between, intrapersonal (socio-demographics and weight status) and neighborhood environmental correlates with objective daily walking and vehicle time. Methods: A subsample of Latinas (n = 87) participating in a health intervention wore an accelerometer and GPS device for at least two valid wear days at baseline. The Personal Activity Location and Measurement System (PALMS) software estimated daily walking and vehicle time. Participants' anthropometrics were measured, and they completed a survey assessing socio-demographic characteristics and perceived neighborhood environment. Generalized linear mixed models examined main effects and interactions of four intrapersonal and five environmental factors on daily walking and vehicle time. Results: On average, participants walked 16 min/day and spent 69 min/day in a vehicle. Overweight/obesity was negatively associated with walking time (p = .04) and positively associated with vehicle time (p = 0.01). Household income was positively associated with vehicle time (p = 0.02). For daily walking time, two interactions were significant: perceived access to destinations X household income (p = 0.01), and perceived sidewalk maintenance X acculturation (p = 0.01). For daily vehicle time, two interactions were significant: perceived access to destinations X weight status (p < 0.001), and perceived safety from crime X education (p = 0.01). Conclusion: Latinas participated in relatively low walking time and high amounts of vehicle time. Findings suggest intrapersonal sub-group differences in the association of the neighborhood environment with walking and vehicle time. Improving neighborhood environments to promote walking and reduce vehicle time may help improve Latinas' overall physical activity. Highlights: Latinas participate in low levels of walking and high amounts of vehicle time. Overweight/obese Latinas had lower amounts of walking time and higher vehicle time. Latinas of higher income had higher amounts of vehicle time. Interaction findings can help improve ecological models specific to Latinas.